PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP KEMANDIRIAN BELAJAR SISWA PADA BIDANG STUDI PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMP NEGERI 5 KOTA SOLOK - Lasri Rahmadia Fitri; Arifmiboy (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The This research is motivated by the low independence of student learning, this can be seen from the teaching and learning process, if a teacher is unable to enter class, students are more likely to carry out activities such as playing, chatting with friends and students who do not have their own initiative. to learn, complain when given assignments, have a tendency to copy the results of the theme's assignments, students are less active, students only speak or answer when asked only in learning. This study aims to overcome the problem of lack of student learning independence, as well as increase student learning independence by using a learning model, namely the Project Based Learning model. The type of research is Quasi Experiment with Posttest Only nonequivalent Control group Design design, the population of this research is the entire class VIII students of SMP Negeri 5 Kota Solok, the sample in this study is class VIII.5 As the Control Class in class VIII.6 As the experimental class, the sampling technique uses Random sampling samples, data collection techniques here using questionnaires, and hypothesis testing analysis techniques using the t-test. After conducting research and testing the hypothesis, the researcher used the One Sample t-test, with the results of Sig. (2-tailed) is greater than 0.05, namely 0.173 > 0.05, so Ho is accepted based on the results of the study. It is concluded that the average student learning independence using the Project Based Learning model equals a score of 75 in the field of study of Islamic Religious Education class VIII at SMP Negeri 5 Kota Solok, and student learning independence using the Project Based Learning model is better than the conventional model. this can be seen based on the results of hypothesis testing using the Independent sample t-test on SPSS 22 software, a sig (2-tailed) value of 0.044 is obtained, which means it is smaller than 0.05 (0.046 <0.05) thus Ho is rejected and Ha is accepted, and is proven by the results of the average experimental class learning independence questionnaire of 72.61 while the average control class learning independence questionnaire is 69.96.